5PSQ-017 Safety of intravenous ferric carboxymaltose in treatment of iron deficiency in children under 2 years with intestinal failure. (2nd March 2018) - Athiana, I; Waldenvik, K; Paulsson, M; Engstrand-Lilja, H; Lundberg, A; Finkel, Y; Nyström, N
Abstract : Background: Children with intestinal failure (IF) are dependent on parenteral nutrition (PN) for normal growth and development. In our practice, individualised PN contain iron-free paediatric trace element mixtures due to the risk of compatibility problems. Children with IF are thus at risk of developing iron deficiency (ID). Furthermore, oral/enteral iron supplementation (IS) is avoided in children with IF because of the reduced absorptive capacity and risk of side-effects. Intravenous (IV) IS with ferric carboxymaltose (FCM) is an approved therapeutic indication for adolescents (>14 years) and adults (see SmPC Ferinject Vifor), however there are no published reports on the effectiveness and safety of IV FCM treatment of ID in children<2 years of age. Purpose: The purpose of this study was to evaluate the safety of IV IS with FCM for patients with IF under the age of 2 years. Material and methods: Part I study: The Swedish Medical Products Agency (MPA) was contacted to collect adverse drug reaction report data for the period 2007 to 2016. Part II study: A retrospective study of the records of 14 children with IF and ID who had been treated with IV FCM before 2 years of age at our tertiary centre for paediatric IF, were performed. Ganzoni's equation was used for calculating the FCM dose, serum levels of haemoglobin, mean corpuscular volume and ferritin were measured before and 1 to 3 months after FCM treatment. Results: Part I: During the 10 years the MPA only received five Adverse Drug Reaction Reports (ADR): Hot flush, hypertension, hypotension and venous thrombosis limb were reported. The ADR data is likely based on treatments for patients>14 years. Part II: All children received one or two doses of FCM administered as intravenous infusion. All children responded to FCM treatment with complete or partial normalisation of biochemical markers for ID. No major or minor adverse events were reported. Conclusion: The treatment of iron deficiency with intravenous ferric carboxymaltose in children<2 years of age with intestinal failure was found effective in the retrospective study of the limited number of patients from our clinic. We did not find any evidence of adverse events. References and/or Acknowledgements: Ferinject SmPC. No conflict of interest